Beastworld : Terrifying monsters and mythical beasts. - Caldwell, S.A. (New York : Scholastic, Inc., 2015)
Step into a world of fascinating, mystical and terrifying beasts from around the globe. Join fearless beast hunter S.A. Caldwell as she tracks down the most elusive creatures from ancient myths, strange sightings and folklore.
A world of monsters -- Beasts of the earth -- Water monsters -- Beasts of the air -- Creatures of the night.
Keywords: Monsters